CORRELATION OF ACSM’S WALKING EQUATION AND DIRECTLY MEASURED VO2MAX IN INDIAN POPULATION: A PILOT STUDY - Ronghe, Rashmi N.; Ashok Gotmare, Neha; Deshpande, Mangala G (International Journal of Clinical and Biomedical Research, 2017)
Purpose of study: American College of Sports and Medicine equation is applied in many cardiovascular centers and sports medicine laboratory. It is used in majority of the commercial software available for exercise testing ACSM has published several metabolic equations for the indirect estimation of VO2max. So the purpose of the study was to find the applicability of ACSM walking equation in Indian population. Aim and Objective: To find out the correlation between actual VO2max and predicted VO2max 18-25 years female in Nagpur. Methodology: All the participants were selected according to sample of convenience and given a thorough explanation of the procedure in the language they understand. Each participant signed written informed consent before participating in the study in the language they could comprehend. Subjects were screened on the basis of selection criteria and PAR-q & you questionnaire. Total 20 participants were selected and demographic and anthropometric data was recorded. In this VO2 max was calculated directly by gas analyzer using AD instrument and indirectly by ACSM’s walking equation and data was analyzed. Result: The mean and standard deviation of directly measured VO2max (ml/kg/min) is 8.6354 and ±4.5557 this shows the range of VO2max for the studied population and VO2max predicted by ACSM walking equation is 38.1891 and ±5.4691. The pearson’s correlation for direct and indirect measurement of VO2max suggested that there is no co-relations with the value (r=0.11, p=, 0.05). Conclusion: The present study concluded that there is no correlation between actual and predicted VO2 max in the studied population and need to develop new regression equation for studied population i.e;ACSM equation is not applicable to the studied population. KEY WORDS: American College of Sports and Medicine walking equation; VO2 max; Indian population.